BOOK REVIEW: Ceramics from Islamic Lands by Oliver Watson, (New York: Thames and Hudson, in association with the al-Sabah Collection, Dar al-Athar alIslamiyyah, Kuwait National Museum, 2004. 512 pp., 930 colour illustrations, 23 appendices, 2 bibliographies, glossary, index, ISBN 0-500-976295, $65.00 hardcover). (2010) - Kolb, Charles C.
No abstract available